Challenges and Effectiveness of Novice Teacher’s Technology Integration in An Islamic Secondary School in North Bali - I Komang Adiartha Negara; Made Aprilia Ayu Adnyani; Made Hery Santosa; Gde Arys Bayu Rewa (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
Technology integration has become an important aspect of English language teaching, especially in private Islamic schools. Although novice teachers are familiar with technology, there is a gap between the potential of technology and its integration in achieving learning objectives and little intensity of previous studies discussing challenges faced by novice teachers’ technology integration in English language teaching in an Islamic private secondary school. This study aimed to evaluate the effectiveness and identify challenges of technology integration by a novice teacher in grade 11 at an Islamic private secondary school in North Bali. It was a case study designed under a qualitative approach, combining semi-structured observations using the Triple-E framework rubric and structured interviews with a single novice teacher. The Triple-E framework showed a score of out 9 of 18 which means technology integration has a moderate level of effectiveness, showing a partial connection between learning objectives and technological tools. The semi-structured interview results exposed several challenges, including technological limitations, workload, school policies regarding mobile phone use, and low student participation. This study highlights the need for institutional support, strategic training, and more flexible policies to maximize the potential of technology in English language teaching. This study is expected to provide new insights into the effectiveness and challenges faced by novice teachers in integrating technology for English language teaching in an Islamic private school context.